Development and dynamics of gut microbial communities of migratory shorebirds in the Western Hemisphere - Grond, Kirsten (Kansas State University, 2017)
Gastrointestinal microbiota play a vital role in maintaining organismal health, through facilitating nutrient uptake, detoxification and interactions with the immune system. Shorebirds vary widely in life-history characteristics, such as habitat, migration and breeding system, but the dynamics of their gut microbial communities are unknown. In my dissertation, I investigated composition and dynamics of gut microbiota in migratory shorebirds from embryos to 10 day old chicks, and determined environment and host-related factors affecting gut microbial communities of adults. First, I tested whether precocial chicks from three species of arctic-breeding shorebirds acquire gut microbiota before or after hatching using next-generation sequencing. In addition, I documented the dynamics of gut microbial establishment. I showed that gut microbiota were absent in shorebird embryos before hatching, but that stable gut communities established within the first three days after hatching. In addition, gut microbiota of young shorebird chicks were more similar to the environmental microbiome than later in life, suggesting that the environment is a likely source for microbial recruitment. After reaching adulthood, shorebirds migrate long distances, potentially exposing them to a wide range of microorganisms. Host phylogeny and environmental factors have both been identified as drivers of gut microbiota composition in birds in previous studies. The second part of my project aimed to compare the relative importance of host and environmental factors that underlie variation in gut microbiota composition in eight species of migratory shorebirds sampled across the North American Arctic. I found that sampling site was the main driver of variation in gut microbiota of Arctic-breeding shorebirds, and that site-related variation in gut microbiota of shorebirds was a result of differences in core bacterial taxa that occurred in more than half of the analyzed samples. A relatively large influence of local environment on gut microbiota composition of chicks and adults lead to the question: how does site affect pathogen prevalence in shorebirds? Migratory behavior has been hypothesized to have evolved as a response to variation in climatic conditions and food availability, to avoid predation, and to reduce risk of exposure to pathogens. The migratory escape hypothesis predicts avoidance of high disease prevalence areas through migration, and has been proposed as one of the main reasons that many bird species migrate to the Arctic for breeding. To test the migratory escape hypothesis in shorebirds, I screened for prevalence of seven known avian pathogens in shorebirds at different stages of migration. I did not detect the majority of pathogens we tested for, with the exception of Campylobacter jejuni and C. coli. Prevalence of C. jejuni in shorebirds was linked to sampling sites but not shorebird species. My dissertation is the first comprehensive study to broadly characterize the gut microbiota in shorebirds. Overall, local environment emerged as an important factor in shaping microbiota composition in Arctic-breeding shorebirds throughout my dissertation research. The role of local environment in shaping gut microbiota invites future investigations of the interactions among shorebirds and the microorganisms present in their environment, as well as the functions gut microbiota perform within their shorebird hosts.
Keywords: Gut microbiota; 16S rRNA gene; Long-distance migration; Early-life development; pathogen prevalence; Arctic-breeding shorebirds